Improved systolic ventricular function with normal myocardial mechanics in compensated cardiac hypertrophy - Okoshi, Katashi [UNESP]; Ribero, H. B.; Okoshi, Marina Politi [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Goncalves, G.; Barros, R.; Cicogna, Antonio Carlos [UNESP] (Japan Heart Journal, Second Dept of Internal Med, 2004)
There is still controversy about the relation between changes in myocardial contractile function and global left ventricular (LV) performance during stable concentric hypertrophy. To clarify this, we analyzed LV function in vivo and myocardial mechanics in vitro in rats with pressure overload-induced cardiac hypertrophy. Male Wistar rats (70 g) Underwent ascending aortic stenosis for 8 weeks (group AAS, n = 9). LV performance wits assessed by transthoracic echocardiography Under anesthesia. Myocardial function Was studied in isolated papillary muscle preparations during isometric contraction. The data were compared with age- and sex-matched sham-operated rats (group C, 11 = 9). LV weight-to-body weight ratio (C: 2.13 +/- 0.14 mg/g; AAS: 3.24 +/- 0.44) LV relative wall thickness (C: 0.18 +/- 0.02; AAS: 0.33 +/- 0.09), and LV fractional shortening (C: 54 +/- 5%; AAS: 70 +/- 8%) were increased in group AAS (P<0.05). Echocardio-graphic analysis also indicated a significant association (r = 0.74 P<0.001) between the percent fractional shortening index and LV relative wall thickness. The performance of AAS isolated In muscle revealed that active tension (C: 6.6 +/- 1.7 g/mm(2); AAS: 6.5 +/- 1.5 g/mm(2)) and maximum rate of tension development (C: 69 +/- 21 g/mm(2)/s AAS: 69 +/- 18 g/mm(2)/s) were not significantly different Front group C (P>0.05). In conclusion, compensated pressure-overload myocardial hypertrophy is associated with preserved myocardial function and increased ventricular performance. The improved LV function might be due to the ventricular remodeling, characterized by an increased relative wall thickness.
Keywords: aortic stenosis; left ventricular hypertrophy; echocardiography; papillary muscle; cardiac function